Finding Everett Ruess : the life and unsolved disappearance of a legendary wilderness explorer - Roberts, David, 1943- (Broadway Books, 2011)
Traces the life of the early twentieth-century adventurer, writer, and watercolor artist, describing his early years as a child prodigy, his solitary journeys through the American Southwest, and his mysterious 1934 disappearance in Navajo country.